2017
DOI: 10.3844/ajassp.2017.930.937
|View full text |Cite
|
Sign up to set email alerts
|

The Rainfall Factor of Climate Change Effects on the Agricultural Environment: A Review

Abstract: The study of the climatic elements is vital for sustainable development of agriculture of a region. Particularly, rainfall temporal analyses for trends, fluctuations and periodicities are necessary as such can indirectly furnish the status of an environment. A trend may be quite instructive for different segments of the human and natural systems. Extreme weather events that can lead to events such as drought, prolonged heat spell and flooding while these can be accessed through the statistical analysis of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Therefore, there is need to distinguish among these causes without erroneously attributing all extreme events to climate change. According to [4] drought is a condition of wide but short-term climatic variation, which results in inadequate rainfall to meet the socio-economic demands of an area in terms of water supply for domestic and industrial uses, agriculture and ecosystem. One of the earliest and most influential interpretations of the cause of drought in the Sahel was that reported by [18], which suggested that reductions in rainfall were the result of human activity.…”
Section: Floods and Droughts Induced By Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is need to distinguish among these causes without erroneously attributing all extreme events to climate change. According to [4] drought is a condition of wide but short-term climatic variation, which results in inadequate rainfall to meet the socio-economic demands of an area in terms of water supply for domestic and industrial uses, agriculture and ecosystem. One of the earliest and most influential interpretations of the cause of drought in the Sahel was that reported by [18], which suggested that reductions in rainfall were the result of human activity.…”
Section: Floods and Droughts Induced By Climate Changementioning
confidence: 99%
“…Evidences from previous researches and past findings have showed that the recent climate change has affected agricultural productivity leading to drastic reduction in the global food production and availability [29] [30] [31]. Climate change is stimulating adverse extreme events like drought and flooding that is causing food shortage and food insecurity in many countries like Somalia, Sudan and other countries that are within the borders of the arid zones [4] [32]. Therefore, it is imperative that extreme events such as floods and droughts will continue to affect agriculture and food production especially African countries if appropriate measure are not taken according to [32] in Figure 1.…”
Section: Floods and Droughts Induced By Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…According to the ACDP index calculated for Poland for 1951-2018, the largest area, i.e., >55%, covered by deficient precipitation in the spring season was determined for 1953,1959, 1963, 1964, 1974, 1976 and 1993. In the same years, precipitation below the multi-year mean was also recorded by other researchers in various regions of Poland, e.g., in March in 1963, 1964, 1974, 1976 and 1993 [8,49]; in April in 1974, 1976 and 1993 [49]; and in May in 1963, 1964 and 1974 [49]. Precipitation deficiency occurs with varying frequency, depending on the degree of its intensity and the region of occurrence, both of which are conditioned by climatic factors [50]. This study shows that deficient precipitation most frequently occurs in central-west and north Poland.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, rainfall is a crucial climate change variable linked to climate extremes such as drought and floods (Ojo & Ilunga, 2017). Past studies point toward an intensifying hydrologic cycle under a warming climate, with a 1 to 3% increase in global mean precipitation per degree rise in temperature (Allen & Ingram, 2002;Held & Soden, 2006).…”
Section: List Of Figuresmentioning
confidence: 99%